Dinamika Penerjemahan Sastra: South of The Slot - Supardi, Bani Nabirah (Buletin Al-Turas, 2017)
Abstract Literary work is an art of language that has function to communicate someone’s idea, feeling, emotion, and soul as a reflection of life. It is nonetheless complicated, since the literary work creation is very personal. Besides requiring creativity and sensitivity, the writer of a literary work also needs to have a wide cultural knowledge and master both languages structure, source and target language. Therefore, a translator as the mediator to convey a message from source language into a target language has significant role. On the one hand, a translator is demanded to keep the source language style and structure of the writer’s source language; on the other hand, a translator is also demanded to convey the readable and acceptable message from the source language into the readers’ target language who have different language and culture. Based on that reasons, this study is aiming at knowing the style and method of translation (formal and dynamic) done by the university students of translation studies. This study uses descriptive-comparative qualitative method. The result of the study is expected to give contribution, especially to improve the quality of translation studies under the Language and Literature Department of Adab and Humanities Faculty of Syarif Hidayatullah State Islamic University of Jakarta.---AbstrakSastra merupakan karya seni bahasa dan alat komunikasi untuk menggambarkan suasana batin, pikiran, perasaan, emosi, imajinasi, dan realitas kehidupan. Untuk menghasilkan sebuah karya sastra tentunya bukanlah suatu hal yang mudah. Proses pembuatan karya sastra yang sangat rumit dan bersifat pribadi menuntut seorang penerjemah sastra memiliki kepekaan rasa dan kreatifitas yang tinggi, memiliki pengetahuan yang luas tentang budaya dan bahasa; Terlebih lagi jika bahasa atau budaya bahasa sumber dan sasarannya sangat jauh berbeda. Dengan demikian, seorang penerjemah sebagai pengalih bahasa dan pesan dari bahasa sumber ke dalam bahasa sasaran, sejatinya memiliki tugas yang sangat berat. Di satu sisi, ia dituntut menjaga gaya dan bahasa sastra yang ingin disampaikan oleh penulis bahasa sumber; Di sisi lain, ia harus bisa menyampaikan pesan/maksud penulis bahasa sumber kepada pembaca yang berbeda latarbelakang bahasa dan budaya. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengetahui gaya bahasa dan metode penerjemahan formal dan dinamis dari hasil terjemahan sastra mahasiswa semester enam dalam menerjemahkan teks sastra South of The Slot. Penelitian ini menggunakan metode dekriptif dengan pendekatan kualitatif. Hasil dari penelitian ini diharapkan dapat memberikan kontribusi, terutama, untuk meningkatkan kualitas pembelajaran penerjemahan sastra pada mahasiswa yang memilih konsentrasi penerjemahan di jurusan Bahasa dan Sastra Inggris, Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta.DOI : 10.15408/bat.v23i2.5415